KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF CONFIDENCE PESERTA DIDIK KELAS XI - Saliha, Putri Pebri (Jurnal Edukasi dan Penelitian Matematika, 2023)
This research attempts to characterize students' self-confidence in terms of their ability to solve mathematical problems. In this study, four questions from the geometry transformation material and 16 items from the self-confidence survey were used to measure the problem solving skills in mathematical of 36 students by class XI MIPA 3. Miles and Huberman's analysis was used to examine the questions, and a triangulation approach was used to check the reliability of sources. data. The research results shown that students with levels in high of self-confidence were able to fulfill all indicators of problem solving, students with moderate levels of self-confidence were able to fulfill two problem solving indicators, and students with low self-confidence. confident can not meet one of the indicators.Keywords– The mathematic problem solving, Self confidence, Learning